Fluorine-containing super-hydrophobic porous super-crosslinked polymer material and application thereof
By embedding fluorine functionalized groups in the supercrosslinked porous polymer, fluorine-containing superhydrophobic porous supercrosslinked polymers is prepared, which solves the problems of unstable structure and harsh reaction conditions of the existing porous materials, and achieves efficient oil-water separation and organic pollutant removal.
Patent Information
- Application Number
- CN202411895233.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-21
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-21
AI Technical Summary
The existing porous materials have unstable structure and harsh reaction conditions, making it difficult to effectively separate oil and water mixtures and remove organic pollutants in water.
Using fluorine-containing superhydrophobic porous supercrosslinked polymer material, the fluorine functionalized groups are embedded into the supercrosslinked porous organic polymer structure through the Fuker reaction to prepare a material with superhydrophobic properties.
The material has a high specific surface area and stable hydrophobic properties. It can efficiently separate oil and water mixtures and remove organic pollutants in water. The separation efficiency is as high as 99.4%, and remains efficient after 10 cycles.
Smart Images

Figure CN119708437A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of super hydrophobic materials, and in particular to a fluorine-containing super hydrophobic porous super cross-linked polymer material and application thereof. Background Art
[0002] With the rapid development of industry, the separation and removal of trace oily mixtures in water has become a major challenge for environmental pollution and governance. Traditional separation methods such as centrifugal separation and gravity sedimentation have the outstanding disadvantages of low efficiency and high energy consumption. Superhydrophobic materials with obvious low surface energy characteristics (water contact angle greater than 150°) show the potential for green and efficient separation of oil-water mixtures and removal of organic pollutants in water. Developing superhydrophobic porous materials is one of the effective ways to solve the above separation problems.
[0003] Superhydrophobic materials should have the physical structure of porous structures with low surface energy and chemical properties. Due to the low surface energy characteristics of fluorinated polymers, researchers have developed a variety of fluorinated functionalized porous materials for oil-water separation and removal of organic pollutants in water in recent years, such as metal organic framework materials (CN 111333854 A), covalent organic frameworks (Journal of Hazardous Materials 411 (2021): 125190.), aerogels (AIChE Journal 68.6 (2022): e17619.), etc. However, metal organic frameworks are unstable in water, which can lead to the collapse of pore structures. The preparation of covalent organic framework materials requires expensive raw materials and harsh reaction conditions, and the adsorption capacity of activated carbon decreases with the use time.
[0004] Hypercrosslinked porous polymers weave monomers and crosslinkers into a polymer network with a stable structure and a large specific surface area through Friedel-Crafts reaction. This structure gives it excellent chemical and thermal stability. Hypercrosslinked polymers have the advantages of simple synthesis, wide monomer selectivity, no need to design connecting functional groups, low solvent and catalyst costs, and large-scale preparation. Summary of the invention
[0005] In order to solve the problems of unstable porous material structure and harsh reaction conditions in the prior art, the present invention provides a fluorine-containing super-hydrophobic porous super-crosslinked polymer material and its preparation method and application. The present invention embeds low surface energy fluorine functional groups into a super-crosslinked porous organic polymer structure, giving the material super-hydrophobic properties. The super-hydrophobic porous super-crosslinked porous organic polymer of the present invention can play an important role in oil-water separation and the removal of organic pollutants in water bodies.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a fluorine-containing super-hydrophobic porous super-cross-linked polymer material, wherein the polymer material is prepared by using tetrafluorobenzyl bromide as a cross-linking agent and a π-electron-rich compound capable of undergoing Friedel-Crafts reaction as a monomer.
[0008] The π-electron-rich compounds capable of undergoing Friedel-Crafts reaction include aromatic compounds such as triphenylbenzene, triptycene, tetraphenylmethane, octaphenylsilsesquioxane, triphenylamine, triphenylphosphine, polycyclic aromatic hydrocarbons, etc. The reaction formula is as follows: Figure 7 shown.
[0009] The chemical formula of the polycyclic aromatic hydrocarbon compound is
[0010] Wherein, R is one or more phenyl groups. In a specific embodiment, the polycyclic aromatic hydrocarbon compound is naphthalene.
[0011] Preferably, the solvent that can be used in the above reaction is one of dichloromethane, dichloroethane, chloroform, chloroform, chlorobenzene, and nitrobenzene.
[0012] Preferably, the above reaction uses one of aluminum chloride or ferric chloride as a catalyst.
[0013] Preferably, the molar ratio of the crosslinking agent, the monomer and the catalyst in the above reaction is (3-4):(1-4):(2-18). The amount of the solvent used is: 30-120 mL of solvent should be used for every 1 mmol of the crosslinking agent.
[0014] Preferably, the above reaction is carried out under an inert gas environment.
[0015] The above reaction comprises the following specific steps:
[0016] (1) The crosslinking agent and monomer are stirred and mixed uniformly in a solvent in an inert gas, and aluminum chloride or ferric chloride catalyst is added.
[0017] (2) Under an inert gas environment, the obtained reaction solution is heated to 20-80° C. and reacted for 12-40 hours, and then filtered, washed, and dried in sequence.
[0018] In step (2), the washing process uses dichloromethane and methanol for washing in sequence.
[0019] The drying in step (2) is carried out at 40-80° C. until the product mass is constant.
[0020] The specific surface area of the fluorine-containing super-hydrophobic porous super-cross-linked polymer material prepared by the present invention is 200-400m 2 / g, micropore surface area accounts for more than 75% of the total surface area, pore volume 0.2~0.6cm 3 / g, pore size of 1 to 10nm, can be used as an adsorbent for separation of emulsified oil or non-emulsified oil. For non-emulsified oil, the separation methods in the current technology include gravity separation, flotation skimming and other methods. These methods have high energy consumption and low separation efficiency in practical applications, and the method of the present invention can solve these problems. Under the conditions of surfactant content of 288.8g / L, oil content of 20g / L, and separation time of 2 minutes, the adsorbent has a separation efficiency of higher than 99.4% for 2% V / V water-in-oil (the components of the "oil" are: dichloromethane (DCM), n-hexane (n-Hexane), cyclohexane (CYH), dimethyl sulfoxide (DMSO), ethyl acetate, dichloroethane (DCE), chlorobenzene (CB), petroleum ether (PE) or xylene (Xylene)) solutions of anionic, cationic and neutral surfactants.
[0021] The application of the fluorine-containing super-hydrophobic porous super-cross-linked polymer material in emulsified oil separation is specifically used in the following method: putting the fluorine-containing super-hydrophobic porous super-cross-linked polymer material into the emulsified oil, vortexing for 2 minutes and then filtering to obtain a pure water phase.
[0022] The fluorine-containing super-hydrophobic porous super-cross-linked polymer material can be dried and reused after adsorption is completed, and after the emulsified oil is separated continuously for 10 times, the separation efficiency is still above 99%.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The two structural units of the fluorine-containing super-hydrophobic porous super-cross-linked polymer material of the present invention both have low surface energy, and have the advantages of low-cost and readily available raw materials, a simple preparation process, and the ability to meet actual production needs.
[0025] The contact angle of the fluorine-containing super-hydrophobic porous super-cross-linked polymer material prepared by the present invention can reach more than 160 degrees, and can maintain stable hydrophobic properties under harsh conditions such as strong acid, strong alkali and high temperature.
[0026] The fluorine-containing super-hydrophobic porous super-cross-linked polymer material prepared by the present invention has uniform internal pore size and large specific surface area (specific surface area 200-400m 2 / g, micropore surface area accounts for more than 75% of the total surface area, pore volume 0.2~0.6cm 3 / g, pore size of 1-10nm), it can separate a variety of emulsified oils (such as water-in-oil (organic pollutants) mixtures, with a separation efficiency of more than 99%. After 10 cycles of recycling, it can still maintain its original oil-water separation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a scanning electron microscope image of the polymer material prepared in Example 1;
[0028] Figure 2 (A) is a carbon nuclear magnetic resonance spectrum of the polymer material prepared in Example 1; (B) is a fluorine nuclear magnetic resonance spectrum of the polymer material prepared in Example 1;
[0029] Figure 3 The contact angle diagrams of the polymer materials prepared in Example 1, Example 2 and Example 3;
[0030] Figure 4 Schematic diagram of the separation process of the polymer material prepared in Example 1 for CTAB-stabilized O / W dichloromethane / water emulsified oil;
[0031] Figure 5 (A) is a picture of the polymer material of Example 1 of the present invention for demulsification of O / W dichloromethane / water emulsified oil stabilized by CTAB (hexadecyltrimethylammonium bromide); (B) picture during demulsification; (C) picture after demulsification and separation; (D) microscopic picture of the emulsion; (E) microscopic picture after demulsification and separation; (F) oil droplet size distribution diagram in the emulsion stabilized by surfactant under a microscope.
[0032] Figure 6 These are pictures of the polymer material HCP-1 of Example 1 of the present invention demulsifying O / W other organic solvent / water emulsified oil stabilized by CTAB (hexadecyltrimethylammonium bromide); (A, E, I, M, Q) pictures before, during and after the demulsification process; (B, F, J, N, R) microscope pictures of the emulsion; (C, G, K, O, S) microscope pictures after demulsification and separation; (D, H, LPT) oil droplet size distribution diagram in the emulsion stabilized by surfactant under a microscope.
[0033] Figure 7 It is the reaction formula of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the embodiment of the present invention will be clearly described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] A fluorine-containing super-hydrophobic porous super-cross-linked polymer material is used as an adsorbent for separation of emulsified oil or non-emulsified oil. The preparation method of the polymer material specifically comprises the following steps:
[0037] (1) In a three-necked flask, 100 mL of dichloromethane, 3 mmol (0.93 g) of tetrafluorobenzyl bromide, and 2 mmol (0.588 g) of triphenylbenzene were added and stirred for 30 minutes under a nitrogen atmosphere to fully disperse them.
[0038] (2) Add 1.2 g of ferric chloride to the reaction solution of step (1), mix well, heat to 80° C. under a nitrogen environment, and react for 30 hours; after the product is cooled to room temperature, filter with a suction flask and wash the filter cake three times with dichloromethane and methanol in sequence, and dry in an oven at 60° C. for 6 hours to constant weight to obtain a fluorine-containing super-hydrophobic porous super-cross-linked polymer material HCP-2, the structural formula of which is shown below:
[0039]
[0040] The water contact angle of the obtained fluorinated super-hydrophobic porous hyper-cross-linked polymer material was measured by a water contact angle meter and was 170.9° ( Figure 3 ), and its adsorption capacity for dichloromethane is 2.8g / g, that is, each gram of the prepared super hydrophobic powder can adsorb 2.8 grams of dichloromethane. The calculation method of the adsorption capacity is: the prepared fluorine-containing super hydrophobic porous super cross-linked polymer material powder is immersed in an organic solvent and then separated to obtain a saturated adsorption super hydrophobic powder, and the mass of the material after adsorption is subtracted from the mass of the material before adsorption and divided by the mass of the material before adsorption to obtain.
[0041] Figure 1 This is a scanning electron microscope image of the fluorine-containing super-hydrophobic porous super-cross-linked polymer material prepared in Example 1. It can be seen from the image that the polymer material has a very rich and uniform pore structure. Figure 2 These are the carbon nuclear magnetic resonance spectrum and the fluorine nuclear magnetic resonance spectrum of the prepared fluorine-containing superhydrophobic porous super-cross-linked polymer material.
[0042] Example 2
[0043] A fluorine-containing super-hydrophobic porous super-cross-linked polymer material is used as an adsorbent for separation of emulsified oil or non-emulsified oil. The preparation method of the polymer material specifically comprises the following steps:
[0044] (1) In a three-necked flask, 100 mL of dichloromethane, 3 mmol (0.93 g) of tetrafluorobenzyl bromide, and 2 mmol (0.508 g) of triptycene were added and stirred for 30 minutes under a nitrogen atmosphere to fully disperse the mixture.
[0045] (2) Add 1.2 g of ferric chloride to the reaction solution of step (1), mix well, heat to 80° C. under a nitrogen environment, and react for 30 hours; after the product is cooled to room temperature, filter with a suction flask and wash the resulting filter cake three times with dichloromethane and methanol in sequence, and dry in an oven at 60° C. for 6 hours to constant weight to obtain a fluorine-containing super-hydrophobic porous super-cross-linked polymer material HCP-4, the structural formula of which is shown below:
[0046]
[0047] The water contact angle of the obtained fluorinated super-hydrophobic porous hyper-cross-linked polymer material was measured by a water contact angle meter and was 162.7° ( Figure 3 ), and its adsorption capacity for dichloromethane is 2.8g / g.
[0048] Example 3
[0049] A fluorine-containing super-hydrophobic porous super-cross-linked polymer material is used as an adsorbent for separation of emulsified oil or non-emulsified oil. The preparation method of the polymer material specifically comprises the following steps:
[0050] (1) In a three-necked flask, 100 mL of dichloromethane, 4 mmol (1.033 g) of tetrafluorobenzyl bromide, and 4 mmol (1.28 g) of tetraphenylmethane were added and stirred for 30 minutes under a nitrogen atmosphere to fully disperse them.
[0051] (2) Add 1.2 g of ferric chloride to the reaction solution of step (1), mix well, heat to 80° C. under a nitrogen environment, and react for 30 hours; after the product is cooled to room temperature, filter with a suction flask and wash the obtained filter cake three times with dichloromethane and methanol in sequence, and dry in an oven at 60° C. for 6 hours to constant weight to obtain a fluorine-containing super-hydrophobic porous super-cross-linked polymer material HCP-5, the structural formula of which is shown below:
[0052]
[0053] The water contact angle of the obtained fluorinated super-hydrophobic porous hyper-cross-linked polymer material was measured by a water contact angle meter and was 164.7° ( Figure 3 ), and its adsorption capacity for dichloromethane is 2.5g / g.
[0054] Example 4
[0055] A fluorine-containing super-hydrophobic porous super-cross-linked polymer material is used as an adsorbent for separation of emulsified oil or non-emulsified oil. The preparation method of the polymer material specifically comprises the following steps:
[0056] (1) In a three-necked flask, 100 mL of dichloromethane, 4 mmol (1.033 g) of tetrafluorobenzyl bromide, and 4 mmol (0.512 g) of naphthalene were added and stirred for 30 minutes under a nitrogen atmosphere to fully disperse them.
[0057] (2) Add 1.2 g of ferric chloride to the reaction solution of step (1), mix well, heat to 80° C. under a nitrogen environment, and react for 30 hours; after the product is cooled to room temperature, filter with a suction flask and wash the resulting filter cake three times with dichloromethane and methanol in sequence, and dry in an oven at 60° C. for 6 hours to constant weight to obtain a fluorine-containing super-hydrophobic porous super-cross-linked polymer material HCP-6, the structural formula of which is shown below:
[0058]
[0059] The water contact angle of the obtained fluorinated superhydrophobic porous hyper-cross-linked polymer material was tested using a water contact angle meter and was found to be 135.7°, and its adsorption capacity for dichloromethane was 1.3 g / g.
[0060] Example 5
[0061] A fluorine-containing super-hydrophobic porous super-cross-linked polymer material is used as an adsorbent for separation of emulsified oil or non-emulsified oil. The preparation method of the polymer material specifically comprises the following steps:
[0062] (1) In a three-necked flask, 100 mL of dichloromethane, 4 mmol (1.033 g) of tetrafluorobenzyl bromide, and 1 mmol (1.344 g) of octaphenylsilsesquioxane were added and stirred for 30 minutes under a nitrogen atmosphere to fully disperse the mixture.
[0063] (2) Add 1.2 g of ferric chloride to the reaction solution of step (1), mix well, heat to 80° C. under a nitrogen environment, and react for 30 hours; after the product is cooled to room temperature, filter with a suction flask and wash the filter cake three times with dichloromethane and methanol in sequence, and dry in an oven at 60° C. for 6 hours to constant weight to obtain a fluorine-containing super-hydrophobic porous super-cross-linked polymer material HCP-7, the structural formula of which is shown below:
[0064]
[0065] The water contact angle of the obtained fluorinated superhydrophobic porous hyper-cross-linked polymer material was tested using a water contact angle meter and was found to be 161.4°, and its adsorption capacity for dichloromethane was 1.4 g / g.
[0066] Example 6
[0067] A fluorine-containing super-hydrophobic porous super-cross-linked polymer material is used as an adsorbent for separation of emulsified oil or non-emulsified oil. The preparation method of the polymer material specifically comprises the following steps:
[0068] (1) In a three-necked flask, 100 mL of dichloromethane, 3 mmol (0.93 g) of tetrafluorobenzyl bromide, and 2 mmol (0.524 g) of triphenylphosphine were added and stirred for 30 minutes under a nitrogen atmosphere to fully disperse the mixture.
[0069] (2) Add 1.2 g of ferric chloride to the reaction solution of step (1), mix well, heat to 80° C. under a nitrogen environment, and react for 30 hours; after the product is cooled to room temperature, filter with a suction flask and wash the obtained filter cake three times with dichloromethane and methanol in sequence, and dry in an oven at 60° C. for 6 hours to constant weight to obtain a fluorine-containing super-hydrophobic porous super-cross-linked polymer material HCP-1, the structural formula of which is shown below:
[0070]
[0071] The water contact angle of the obtained fluorinated superhydrophobic porous hyper-cross-linked polymer material was tested using a water contact angle meter and was found to be 153.7°, and its adsorption capacity for dichloromethane was 1.14 g / g.
[0072] Example 7
[0073] A fluorine-containing super-hydrophobic porous super-cross-linked polymer material is used as an adsorbent for separation of emulsified oil or non-emulsified oil. The preparation method of the polymer material specifically comprises the following steps:
[0074] (1) In a three-necked flask, 100 mL of dichloromethane, 3 mmol (0.93 g) of tetrafluorobenzyl bromide, and 2 mmol (0.502 g) of triphenylamine were added and stirred for 30 minutes under a nitrogen atmosphere to fully disperse the mixture.
[0075] (2) Add 1.2 g of ferric chloride to the reaction solution of step (1), mix well, heat to 80° C. under a nitrogen environment, and react for 30 hours; after the product is cooled to room temperature, filter with a suction flask and wash the obtained filter cake three times with dichloromethane and methanol in sequence, and dry in an oven at 60° C. for 6 hours to constant weight to obtain a fluorine-containing super-hydrophobic porous super-cross-linked polymer material HCP-3, the structural formula of which is shown below:
[0076]
[0077] The water contact angle of the obtained fluorinated superhydrophobic porous hyper-cross-linked polymer material was tested using a water contact angle meter and was found to be 151.3°, and its adsorption capacity for dichloromethane was 1.05 g / g.
[0078] Comparative Example 1
[0079] A method for preparing an oil adsorbent comprises the following steps:
[0080] (1) In a three-necked flask, 100 mL of dichloromethane, 3 mmol (150 μL) of dimethoxymethane, and 2 mmol (0.588 g) of triphenylbenzene were added and stirred for 30 minutes under a nitrogen atmosphere to fully disperse them.
[0081] (2) Add 1.2 g of ferric chloride to the reaction solution of step (1), mix well, heat to 80° C. under a nitrogen environment, and react for 30 hours; after the product is cooled to room temperature, filter with a suction flask and wash the filter cake three times with dichloromethane and methanol in sequence, and dry in an oven at 60° C. for 6 hours to constant weight to obtain an adsorbent.
[0082] The water contact angle of the adsorbent was tested by a water contact angle meter and was found to be 77°. Its adsorption capacity for dichloromethane was 0.59 g / g.
[0083] Application Examples
[0084] 288.8 g of surfactant cetyltrimethylammonium bromide (CTAB) was dispersed in 1000 g of water, and after it was completely dissolved, 20 g of dichloromethane was added, and the mixture was stirred continuously for 2 hours at room temperature with a stirring speed of 2000 rpm to obtain a CTAB-stabilized O / W dichloromethane / water emulsified oil.
[0085] like Figure 4 As shown, 0.5 g of the adsorbent prepared in Examples 1 to 7 and Comparative Example 1 was directly placed in 200 mL of an oil-water mixture (O / W dichloromethane / water emulsified oil), shaken evenly, and the resulting mixed solution was filtered after 2 minutes. At the same time, a control group 1 was set up - no adsorbent was added, and the obtained solution was analyzed by visible light microscopy to determine its oil content; at the same time, the separation efficiency after 10 separations was studied, and the results obtained were as follows:
[0086] The separation efficiency of the control group 1 for the CTAB-stabilized emulsified oil was 0.3%, and the separation efficiency of the adsorbent of Example 1 for the CTAB-stabilized O / W dichloromethane / water emulsified oil was 99.6%. In addition, the separation efficiency of the adsorbent for the above emulsified oil after 10 consecutive separations was 99.3%; wherein, Figure 5 A to 5E are graphs showing the changes of the adsorbent of Example 1 before and after the adsorption of CTAB-stabilized O / W dichloromethane / water emulsified oil. It can be seen from the graphs that the oil droplets of the emulsified oil basically disappear after the adsorption.
[0087] The adsorbent of Example 2 had a separation efficiency of 99.8% for CTAB-stabilized O / W dichloromethane / water emulsified oil. In addition, the adsorbent had a separation efficiency of 99.7% after 10 consecutive separations of the emulsified oil.
[0088] The adsorbent of Example 3 has a separation efficiency of 99.7% for CTAB-stabilized O / W dichloromethane / water emulsified oil. In addition, the adsorbent has a separation efficiency of 99.5% after 10 consecutive separations of the emulsified oil.
[0089] The adsorbent of Example 4 had a separation efficiency of 99.4% for CTAB-stabilized O / W dichloromethane / water emulsified oil. In addition, the adsorbent had a separation efficiency of 99.3% after 10 consecutive separations of the emulsified oil.
[0090] The adsorbent of Example 5 had a separation efficiency of 99.6% for CTAB-stabilized O / W dichloromethane / water emulsified oil. In addition, the adsorbent had a separation efficiency of 99.4% after 10 consecutive separations of the emulsified oil.
[0091] The adsorbent of Example 6 had a separation efficiency of 99.8% for CTAB-stabilized O / W dichloromethane / water emulsified oil. In addition, the adsorbent had a separation efficiency of 99.4% after 10 consecutive separations of the emulsified oil.
[0092] The adsorbent of Example 7 had a separation efficiency of 99.7% for CTAB-stabilized O / W dichloromethane / water emulsified oil. In addition, the adsorbent had a separation efficiency of 99.5% after 10 consecutive separations of the emulsified oil.
[0093] The adsorbent of Comparative Example 1 has a separation efficiency of 13.2% for CTAB-stabilized O / W dichloromethane / water emulsified oil. In addition, the adsorbent has a separation efficiency of 8.1% after 10 consecutive separations of the emulsified oil.
[0094] The adsorbent of Example 1 was used to separate the CTAB-stabilized O / W chlorobenzene / water emulsified oil, and the separation efficiency was 99.5%. The separation efficiency of the adsorbent after 10 consecutive separations of the emulsified oil was 99.4%.
[0095] The adsorbent of Example 1 was used to separate the CTAB-stabilized O / W dichloroethane / water emulsified oil, and the separation efficiency was 99.6%. The separation efficiency of the adsorbent after 10 consecutive separations of the emulsified oil was 99.5%;
[0096] The adsorbent of Example 1 was used to separate the CTAB-stabilized O / W xylene / water emulsified oil, and the separation efficiency was 99.8%. The separation efficiency of the adsorbent after 10 consecutive separations of the emulsified oil was 99.7%;
[0097] The adsorbent of Example 1 was used to separate the CTAB-stabilized O / W petroleum ether / water emulsified oil, and the separation efficiency was 99.5%. The separation efficiency of the adsorbent after 10 consecutive separations of the emulsified oil was 99.4%.
[0098] The adsorbent of Example 1 was used to separate the CTAB-stabilized O / W n-hexane / water emulsified oil, and the separation efficiency was 99.6%. The separation efficiency of the adsorbent after 10 consecutive separations of the emulsified oil was 99.4%.
[0099] The adsorbent of Example 1 was used to separate the CTAB-stabilized O / W cyclohexane / water emulsified oil, and the separation efficiency was 99.7%. The separation efficiency of the adsorbent after 10 consecutive separations of the emulsified oil was 99.5%.
[0100] Figure 6 The graph is a change diagram of the adsorbent of Example 1 before and after adsorption of the above-mentioned CTAB-stabilized O / W organic pollutants (chlorobenzene, dichloroethane, xylene, petroleum ether, and n-hexane / water emulsified oil. It can be seen from the figure that the oil droplets of the emulsified oil after adsorption basically disappear.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A fluorine-containing super-hydrophobic porous super-cross-linked polymer material, characterized in that: The polymer material is prepared by reacting tetrafluorobenzyl bromide as a crosslinking agent with a compound rich in π electrons and capable of undergoing Friedel-Crafts reaction as a monomer under the action of a catalyst.
2. A fluorine-containing super-hydrophobic porous super-cross-linked polymer material according to claim 1, characterized in that: The compounds rich in π electrons and capable of undergoing Friedel-Crafts reaction include: triphenylbenzene, triptycene, tetraphenylmethane, octaphenylsilsesquioxane, triphenylamine, triphenylphosphine, and polycyclic aromatic hydrocarbons.
3. The fluorine-containing super-hydrophobic porous super-cross-linked polymer material according to claim 1, characterized in that: The catalyst is aluminum chloride or ferric chloride.
4. The fluorine-containing super-hydrophobic porous super-cross-linked polymer material according to claim 1, characterized in that: The molar ratio of the crosslinking agent, the monomer and the catalyst in the reaction is (3-4): (1-4): (2-18).
5. The fluorine-containing super-hydrophobic porous super-cross-linked polymer material according to claim 1, characterized in that: The reaction is carried out under an inert gas environment.
6. The fluorine-containing super-hydrophobic porous super-cross-linked polymer material according to claim 1, characterized in that: The reaction steps include: (1) stirring and mixing a crosslinking agent and a monomer in a solvent in an inert gas to be uniform, and adding a catalyst to obtain a reaction solution; (2) Under an inert gas environment, the obtained reaction solution is heated to 20-80° C. and reacted for 12-40 hours, and then filtered, washed, and dried in sequence.
7. The fluorine-containing super-hydrophobic porous super-cross-linked polymer material according to claim 6, characterized in that: The solvent in step (1) is one of dichloromethane, dichloroethane, chloroform, chloroform, chlorobenzene and nitrobenzene.
8. Use of the fluorine-containing super-hydrophobic porous super-cross-linked polymer material according to any one of claims 1 in separation of emulsified oil or non-emulsified oil.
9. The use according to claim 8, characterized in that: The emulsified oil is an oil-in-water solution stabilized by a surfactant.
10. The use according to claim 9, characterized in that: The oil-in-water is water-in-dichloromethane, n-hexane, cyclohexane, dimethyl sulfoxide, ethyl acetate, ethylene dichloride, chlorobenzene, petroleum ether or xylene.
Citation Information
Patent Citations
Super-hydrophobic porous coordination polymer based on partially fluorinated organic ligand, preparation method and application thereof
CN111333854A
Preparation and application of hydrophobic porous organic polymer material
CN108912312A
Preparation method of super-cross-linked polymer
CN109485831A
Preparation method of super-hydrophobic high-specific-surface-area microporous polymer adsorption material
CN109880150A
Super-hydrophobic porous organic polymer containing alkyl chains and preparation method and application of super-hydrophobic porous organic polymer containing alkyl chains
CN110437425A